Genetically-engineered Salmonella typhimurium expressing TIMP-2 as a therapeutic intervention in an orthotopic glioma mouse model. (1st October 2018) - Wen, Min; Zheng, Jin Hai; Choi, Jin Myung; Pei, Jian; Li, Chun-Hao; Li, Song-Yuan; Kim, In-Young; Lim, Sa-Hoe; Jung, Tae-Young; Moon, Kyung-Sub; Min, Jung-Joon; Jung, Shin
Abstract: Glioma is one of the most devastating and refractory cancers. The main factors underlying therapeutic failure include extremely invasive characteristics and lack of effective methods for drug delivery. Attenuated Salmonella strains presented a high concentration of tumor targets in various types of cancer models, suggesting a role as potential vectors for drug delivery. In this study, we genetically engineered an attenuated strain of Salmonella as an anti-invasive vector for the targeted delivery and expression of tissue inhibitor of metalloproteinases 2 (TIMP-2) in an orthotopic nude mouse model of glioma. The bioluminescence signals related to tumor size significantly declined in the TIMP-2-expressing Salmonella (SLpTIMP-2)-treated group compared with the control group. Compared with the control group with a survival rate of an average of 33 days, the SLpTIMP-2 group showed an extended survival rate by nearly 60% and lasted an average period of 53 days with TIMP-2 induction. These results indicated the promising therapeutic potential of S. typhimurium for targeted delivery and secretion of TIMP-2 in glioma. Highlights: Intracranial injection of Salmonella has been demonstrated to be a more effective than tail vein injection. Treatment with TIMP-2-expressing bacteria showed down regulation of MMP-2 in orthotopic glioma. TIMP-2-expressing bacteria significantly inhibited tumor growth and elongated animal survive.